Proteomic analysis reveals candidate molecules to mediate cortical pathology and identify possible biomarkers in an animal model of multiple sclerosis - Silva, Berenice Anabel; Leal, María Celeste; Farias, María Isabel; Nava, Agustín; Galván, Daniela Inés; Fernandez, Elmer; Pitossi, Fernando Juan; Ferrari, Carina Cintia (Frontiers in Immunology, 2025)
IntroductionMultiple Sclerosis (MS) is a complex neurodegenerative disease marked by recurring inflammatory episodes, demyelination, axonal damage, and subsequent loss of function. MS presents a wide range of clinical courses, with the progressive forms leading to irreversible neurological disability. Cortical demyelinating lesions are central to the pathology of these progressive forms, gaining critical importance in recent decades due to their strong correlation with physical disability and cognitive decline. Despite this, the underlying mechanisms driving cortical lesion formation remain poorly understood, and no specific treatments are currently available. A significant challenge lies in the lack of animal models that accurately mirror the key characteristics of these lesions.MethodsWe developed a focal cortical animal model that replicates many features of cortical lesions, including cognitive impairment. This study focuses on conducting proteomic analyses of both the cortical lesions and cerebrospinal fluid (CSF) from these animals, aiming to identify key proteins and biomarkers that could be validated in MS patients. ResultsProteomic differences between frontal cortex tissue and CSF were observed when comparing experimental animals with controls. Among the identified proteins, some have been previously described in MS patients and animal models, while others represent novel discoveries. Notably, we identified two proteins, S100A8 and orosomucoid-1, that were highly expressed in both regions. ConclusionsThese findings suggest that the prognostic molecules identified in this model could facilitate the discovery of new biomarkers or key molecules relevant to MS, particularly in the cortical lesion that mainly characterized the progressive forms of the disease.